Bridging chemical- and bio-catalysis: high-value liquid transportation fuel production from renewable agricultural residues. Issue 3 (7th December 2016) - Xue, Chuang; Liu, Min; Guo, Xinwen; Hudson, Elton P.; Chen, Lijie; Bai, Fengwu; Liu, Fangfang; Yang, Shang-Tian
Abstract : Catalytic conversion of lignocellulosic biomass to high-value transportation petrol, jet and diesel fuels is of great importance to develop versatile renewable energy and boost the rural economy, thus it is receiving worldwide attention. Abstract : Catalytic conversion of lignocellulosic biomass to high-value transportation petrol, jet and diesel fuels is of great importance to develop versatile renewable energy and boost the rural economy, thus it is receiving worldwide attention. However, the state-of-the-art processes still suffer from a low efficiency in yield and productivity, which hinders the progress of its commercialization. Thus, it is essential to explore the consolidated catalytic reaction and refinery process. Here we report an advanced approach/process that could continuously produce long-chain (C5 –C15 ) ketones from lignocellulosic biomass in a cascade mode by integrating several bio- and chemical catalysis reactions/processes, which exhibits a high efficiency and stable conversion rate. This technology consolidated the acetone–butanol–ethanol (ABE) fermentation, palladium catalyzed alkylation and in situ product recovery, allowing the catalytic reaction to proceed consistently and smoothly. The remarkable conversion properties are mainly attributed to the excellent compatible linkage of chemical catalysis with biosynthesis and process design to stabilize the Pd catalytic reaction. This validated strategy for the rational process design and integration of chemical- and bio-catalysis offers great demonstration in producing high-value transportation biofuels derived from agricultural residues.